Balancing act: Studying the effect of perch space allowance on welfare in Canadian laying strain pullets raised in floor pens with access to a single-tier perch system to 18 wk of age - Carolin A.B. Adler; Tory Shynkaruk; Samantha McPhee; Kailyn Buchynski; Adelle Herr; Eugenia Herwig; Karen Schwean-Lardner (Poultry Science)
The rearing environment for pullets should mirror their later production environment as closely as possible. However, existing perch space recommendations are based on data for laying hens rather than pullets. This study explores the impact of perch space allowances on the welfare of Canadian laying strain pullets raised to 18 wk. Two trials were conducted with 1,032 Lohmann Brown-Lite (LB) and LSL-Lite (LW) pullets each. A randomized complete block (trial) design was used with a 4 (perch space) × 2 (strain) factorial arrangement. Birds were raised in 16 floor pens (3 × 3 m each; 897.67 cm2 per bird). Wooden perches were provided from d 1, allowing 6, 9, 12, or 15 cm perch space per pullet. Data were tested for normality, and log+1 transformed if necessary. Significance was declared at P≤0.05. Data were collected for basic health and functioning (body weight, mortality, pullet width, keel bone damage, and tibia bone parameters), affective states (comb damage, heterophil-to-lymphocyte (H/L) ratios, and behavior), and natural living (perch usage and jumping success). Perch space did not affect mortality, keel bone damage, tibia breaking strength, comb damage, or H/L ratios. At 16 and 18 wk, LB body weight slightly increased while the LW body weight decreased with increasing perch space (P=0.05 and 0.02). At 3 wk, pullets spent a higher percentage of time wing flapping on the perch when provided 15 cm compared to 6 cm (P=0.04). During the scotoperiod at 18 wk, a higher percentage of birds perched with 12 and 15 cm perch space than 6 cm (P<0.01). Pullet width at 18 wk was 12.52 cm (sitting) and 11.66 cm (standing) for the LB and 13.85 cm (sitting) and 12.94 cm (standing) for the LW. Overall, perch space allowance had minor effects on the measured welfare indicators. Based on pullet width, a minimum of 12.5 cm for LW and 13.9 cm for LB pullets should be provided to allow all pullets to sit on the perch simultaneously.